QUALITY OF VERMICOMPOST AND VERMIWASH FROM HOUSEHOLD WASTE BASED ON SAGO PULP AND COW MANURE - Kisworo Kisworo; Haryati B. Sutanto; Irene Putri Permatasari (Universitas Medan Area, 2026)
The processing of household organic waste through vermicomposting has the potential to produce fertilizers with higher nutrient content compared to conventional methods. This study aims to analyze the effect of adding sago pulp and cow manure as media on the quality of vermicompost and vermiwash derived from household organic waste using Eisenia fetida worms. The experiment was conducted using five treatments with five replications. Observed parameters included media moisture, temperature, pH, changes in color and texture, odor, earthworm biomass, and the contents of nitrogen (N) and phosphorus (P). Data were analyzed descriptively by correlating observational results with laboratory analyses of vermicompost and vermiwash. The results indicate that the treatment consisting of sago pulp with the addition of 50% household organic waste (SP+HOW 50%) produced nitrogen and phosphorus contents that met the requirements of SNI 7763:2024. Overall, the findings indicate that vermicomposting using sago pulp and household organic waste can be applied as a sustainable approach to organic waste management while producing organic fertilizer derived from local resources.